PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GUIDE PADA MASA PANDEMI COVID 19 DI NUSA PENIDA KLUNGKUNG - Ni Putu Medhavi Nityasya; Ni Ketut Murdani; I Made Arjana (Nusantara Hasana Journal, 2022)
This study aims to find empirical evidence regarding the effect of work stress and motivation on the performance of Guide at Nusa Penida Klungkung during the Pandemic Period. Respondents in this study were employees who worked as Tout Guides on Nusa Penida Klungkung. The number of employees sampled in this study amounted to 35 people. Hypothesis testing in this study used multiple regression analysis techniques. The results showed that work stress has a significant influence on of Guide Tour in Nusa Penida performance. So is significant motivation towards Guide performance. The study also showed that the relationship between work stress and motivation has a simultaneous significant influence on Guide Tour Nusa Penida performance.